Carbon leakage: an overview - Marcu, Andrei; Egenhofer, Christian; Roth, Susanna; Stoefs, Wijnand (Brussels, 2013)
"The result of asymmetrical carbon policies, especially carbon pricing, and the resulting carbon cost, carbon leakage affects the international competitive position of some EU industry and could displace production and/or investment, and the emissions of the activities displaced. The issue is central to the discussions on climate policy, given the confluence of issues that are currently being debated, including the 2030 Energy and Climate Framework and the review of the EU carbon leakage list by 2014. This Special Report, prepared as a background paper by the CEPS Carbon Market Forum for the Carbon Leakage Project, should be seen as a primer that provides policy-makers, politicians, regulators and industry with a document that is easily readable and yet sufficiently rigorous to be illuminating, and which outlines the issues and why they are important."